Establishment of an encapsulation technique for in vitro propagated plantlets of banana (Musa AAA) cv. Albeely - H. A. Othman, Mohammed; A. Ali, Mohamed; A. Abdellatif, Igbal (Gezira Journal of Agricultural Science; Vol 10 No 2 (2012), 2023)
SHORT NOTE Edible triploid banana are vegetatively propagated by suckers because viable seeds are not usually produced in these cultivars. New and effective means of propagating bananas would be advantageous, over the conventional use of sucker material, for germplasm maintenance, exchange and transportation. In vitro culture of floral apices or vegetative meristem is the most promising propagation method available to date (Ganapathi et al ., 1992). Synthetic seeds are defined as artificially encapsulated somatic embryoes, shoot buds, cell aggregates, or any other tissue that can be used for sowing as a seed, or other in vitro -derived tissue capable of conversion into plantlets under in vitro or in vivo conditions and that retain this potential after storage (Ganapathi et al., 1992). Nevertheless, to reach such objective, the encapsulation technique must be firstly improved regarding its composition and conditions for short term storage. In the case of banana ( Musa AAA), the use of synthetic seed technique may improve the quality of the plantlets and reduce the production costs. This technique was successfully employed in the cvs. ‘Basrai’ by Ganapathi et al. (1992). The successful demonstration of encapsulation of tissue culture derived propagules in a nutrient gel has initiated a new line of research on synthetic seeds. The use of artificial seeds makes the tissue culture techniques more advantageous due to rapid multiplication, maintained genetic uniformity of plants, direct delivery propagules to the field, thus eliminating transplant and omitting the acclimatization steps, reduction of storage space, reduction in costs of vegetatively propagated plants and reduction in the breeding cycle (Maruyama et al ., 1996). Therefore, the objectives of this study were to establish a technology for synthetic seeds production using tissue culture plantlets and test the viability of the developed synthetic seeds of the banana cv. “Albeely"